Kimyo va kimyoviy texnologiyalar: SYNTHESIS OF POLYCARBOXYLATE PLASTICIZER BASED ON ACRYLIC ACID AND APEG AND ITS GEL CHROMATOGRAPHIC ANALYSIS - Djalilov, Abdulakhat; Sottikulov, Elyor; Karimov, Masud; Boymirzayev, Azamat (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Objective. The purpose of this work is not only to develop a method for synthesizing a new plasticizer but also to study its properties using gel chromatography, which will allow for the optimization of its use in concrete production. Methods. The research includes the synthesis of polycarboxylate-based plasticizers and the determination of their polyelectrolyte properties using gel chromatography. The work employed multifaceted experimental approaches aimed at determining the molecular mass and structure of the new products. The distribution of molecular masses, hydrodynamic parameters, and polyelectrolyte properties of the synthesized copolymers are discussed. Results. The study successfully synthesized a new polycarboxylate-based plasticizer and determined its molecular mass and structure using gel chromatography. The copolymer's molecular mass was 10 kDa, and the monomer fraction was 1.8 kDa. The plasticizer improved concrete mixture properties, enhancing flowability, hardening time, and strength. Conclusion. Research has been carried out on the synthesis of plasticizers based on polycarboxylates and the determination of their polyelectrolyte properties using gel chromatography. The distribution of molecular weights, hydrodynamic parameters, and polyelectrolyte properties of the copolymers obtained during the synthesis are discussed.